Fe2O3 / GCN / ICG / DHA nano-composite and preparation method and application thereof
By designing Fe2O3/GCN/ICG/DHA nanocomposites, using their photothermal, photodynamic and chemical dynamic properties, the side effects of existing malignant tumor treatment methods and limited anti-tumor effects are solved, and efficient combined tumor treatment is achieved Effect.
Patent Information
- Application Number
- CN202411548520.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-18
AI Technical Summary
The existing malignant tumor treatment methods have side effects and complications, and a single novel therapy is difficult to fully cover all the mutation and escape mechanisms of the tumor, resulting in limited anti-tumor effects.
A Fe2O3/GCN/ICG/DHA nanocomposite was designed, and prepared by high-temperature polymerization and in-situ synthesis. The ferrous oxide/carbon nitride nanosheets were used as carrier to load the photosensitizer ICG and load the drug DHA to build a photosensitive agent. Nanocomposites with thermal/photodynamic/chemical dynamic properties.
The nanocomplex produces a warming effect and ROS under 808nm near-infrared laser irradiation. Fe2+ reacts with DHA to produce C-center free radicals, effectively killing tumor cells and achieving efficient combined tumor treatment effects.
Smart Images

Figure CN119454949A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanocomposites, and in particular to a Fe2O3 / GCN / ICG / DHA nanocomposite and a preparation method and application thereof. Background Art
[0002] Malignant tumors pose a major challenge to global public health and pose a serious threat to human health and life. Currently, there are three main traditional therapies for the treatment of malignant tumors: surgery, radiotherapy, and chemotherapy. While these traditional therapies can help inhibit tumor growth to a certain extent, they are also accompanied by a series of side effects and complications, which limit their application in the treatment of malignant tumors. To overcome these shortcomings, it is necessary to continuously explore and research new treatment methods, such as targeted therapy, phototherapy, immunotherapy, and gene therapy, in order to enhance tumor targeting capabilities, improve tumor treatment efficacy, and reduce systemic toxic side effects. Among these new therapies, phototherapy (photothermal therapy / photodynamic therapy) is a new non-invasive treatment for malignant tumors with the advantages of high specificity, low toxicity, and a short treatment cycle.
[0003] Indocyanine green (ICG), a novel photosensitizer approved by the US Food and Drug Administration, is widely used in clinical near-infrared fluorescence imaging. ICG exhibits excellent photothermal properties and can efficiently generate potent reactive oxygen species (ROS). These properties make ICG promising for broad medical applications. However, ICG's readily photodegradable nature, rapid blood clearance, and low tumor accumulation make it a promising candidate for biosafety and high-drug-loading nanocarriers to enhance therapeutic efficacy.
[0004] Due to the complexity and heterogeneity of malignant tumors, a single novel therapy is often unable to fully cover all tumor mutations and escape mechanisms, resulting in limited anti-tumor effects. The current trend in the field of novel tumor treatment research has gradually shifted from focusing on a single novel therapy to combination therapy to achieve efficient tumor treatment. Several studies have shown that combining phototherapy with other novel therapies has significant anti-tumor effects and can effectively inhibit tumor recurrence and metastasis. Among the many novel therapies, chemodynamic therapy (CDT) is a novel anti-tumor therapy. The anti-tumor mechanism of CDT is mainly to utilize the Fenton or Fenton-like reaction involving metal ions to produce highly harmful reactive oxygen species (such as hydroxyl radicals and C-center free radicals), thereby inducing tumor cell apoptosis.
[0005] Dihydroartemisinin (DHA) is an antimalarial drug extracted from Artemisia annua. Recent studies have shown that it has strong anti-tumor effects in vivo. The molecular structure of dihydroartemisinin contains peroxide bonds. Ferrous ions can cleave the peroxide bonds of DHA to produce C-centered free radicals, which can cause damage and apoptosis of tumor cells. However, DHA's poor water solubility and insufficient iron supply in solid tumors hinder its application in tumor chemodynamic therapy. Therefore, designing a nanomaterial-based drug delivery system to improve DHA uptake efficiency and iron ion concentration in tumor sites is essential to unleash the anti-tumor properties of DHA. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to provide a Fe2O3 / GCN / ICG / DHA nanocomposite and a preparation method and application thereof. The nanocomposite can be applied to the field of tumor drugs.
[0007] To solve the above technical problems, according to one aspect of the present invention, a Fe2O3 / GCN / ICG / DHA nanocomposite is provided, which comprises: ferric oxide / carbon nitride (Fe2O3 / GCN) as a carrier, the carrier is loaded with a photosensitizer indocyanine green (ICG) and a drug dihydroartemisinin (DHA).
[0008] According to another aspect of the present invention, provided is a method for preparing the Fe2O3 / GCN / ICG / DHA nanocomposite, comprising: Step 1, preparing carbon nitride nanosheets (GCN); Melamine powder was calcined in a muffle furnace at 520°C ± 5°C. The calcined product was ground and dissolved in deionized water. After sonication, it was freeze-dried to obtain carbon nitride nanosheets. Step 2, preparing ferric oxide / carbon nitride (Fe2O3 / GCN); The carbon nitride nanosheets (GCN) and FeCl3·6H2O obtained in step 1 were dissolved in anhydrous ethanol, mixed evenly, and dried; the dried powder was transferred to a muffle furnace and heated to 350°C ± 5°C for reaction to obtain a product, which was dissolved in deionized water and transferred to a polytetrafluoroethylene reactor at 160°C ± 5°C for complete reaction, and the obtained product was washed with ethanol and deionized water, and the precipitate obtained after washing was dried to obtain Fe2O3 / GCN; Step 3, preparing ferric oxide / carbon nitride / indocyanine green (Fe2O3 / GCN / ICG); Fe2O3 / GCN and indocyanine green were dissolved in methanol solution respectively, the two solutions were mixed and stirred in the dark, the obtained reaction product was centrifuged and the precipitate was collected, the precipitate was washed and dried overnight to obtain Fe2O3 / GCN / ICG.
[0009] Step 4, preparing ferric oxide / carbon nitride / indocyanine green / dihydroartemisinin (Fe2O3 / GCN / ICG / DHA); Fe2O3 / GCN / ICG and dihydroartemisinin were dissolved in anhydrous ethanol respectively, the two solutions were mixed and stirred, and the obtained reaction product was washed and dried to obtain Fe2O3 / GCN / ICG / DHA solid.
[0010] Furthermore, in step 1, 3.0 g of melamine was weighed and placed in a mortar and ground thoroughly; the ground powder was placed in a muffle furnace, heated to 520 ° C at a heating rate of 5 ° C / min, and calcined for 4 h, and then cooled to room temperature to obtain block GCN.
[0011] Furthermore, in step 1, the block GCN was ground into powder, 500 mg was dissolved in 200 mL of deionized water, and then ultrasonicated at 600 W for 6 h and freeze-dried to obtain carbon nitride nanosheets.
[0012] Furthermore, in step 2, 0.6 g of the prepared GCN nanosheets and 0.2 g of FeCl3·6H2O were weighed and dissolved in 20 mL of anhydrous ethanol, stirred at room temperature for 0.5 h to mix evenly, and the stirred solution was placed in a 60°C oven to dry; the powder obtained after drying was transferred to a crucible with a lid and placed in a muffle furnace, and the temperature was increased to 350°C at a heating rate of 5°C / min and reacted for 2 h to obtain a brown-yellow powder reaction product.
[0013] Furthermore, in step 2, the brown-yellow powdered reaction product was dissolved in 15 mL of deionized water and mixed evenly, then transferred to a 15 mL polytetrafluoroethylene reactor and heated at 160°C for 12 h. After cooling to room temperature, it was thoroughly washed with ethanol and deionized water to remove unbound FeCl3·6H2O; finally, the obtained precipitate was placed in a 60°C oven and dried overnight to obtain Fe2O3 / GCN.
[0014] Furthermore, in step three, 10 mg of Fe2O3 / GCN was dissolved in 10 mL of methanol solution and ultrasonically treated for 30 min to obtain solution A, 3 mg of indocyanine green was weighed and dissolved in 10 mL of methanol solution to obtain solution B, and solution B was added to solution A and stirred at 350 rpm in the dark at room temperature for 12 h.
[0015] Furthermore, in step three, the reaction product obtained after stirring the reaction in the dark was centrifuged at 10,000 rpm for 15 min, and the precipitate was collected and washed with anhydrous ethanol and deionized water; the washed product was placed in a 60° C. oven and dried overnight to obtain Fe2O3 / GCN / ICG.
[0016] Furthermore, in step 4, 10 mg of Fe2O3 / GCN / ICG was dispersed in 10 mL of anhydrous ethanol to obtain a Fe2O3 / GCN / ICG solution; 4 mg of dihydroartemisinin was dissolved in 5 mL of anhydrous ethanol and added to the Fe2O3 / GCN / ICG / DHA solution, and stirred at room temperature for 24 h. The reaction product was washed alternately with anhydrous ethanol and deionized water to remove free DHA; and dried at 60°C to obtain a Fe2O3 / GCN / ICG / DHA solid.
[0017] Another aspect of the present invention provides the use of the Fe2O3 / GCN / ICG / DHA nanocomposite in the preparation of anti-tumor drugs.
[0018] The present invention prepares ferric oxide / carbon nitride nanosheets by high-temperature polymerization and in-situ synthesis, uses them as carriers to load the photosensitizer ICG and the drug DHA, and constructs a Fe2O3 / GGCN / ICG / DHA nanocomposite with photothermal / photodynamic / chemodynamic properties.
[0019] The iron ions in Fe2O3 / GCN / ICG / DHA can be reduced to ferrous ions under the condition of high H2O2 in the tumor microenvironment. 2+ It reacts with DHA to produce C-center free radicals that kill tumor cells; in addition, the ICG loaded on Fe2O3 / GCN / ICG / DHA produces a heating effect and generates cytotoxic singlet oxygen under irradiation of 808nm near-infrared laser.
[0020] The multi-effect combined anti-tumor effect of Fe2O3 / GCN / ICG / DHA was evaluated through in vitro, cell and animal experiments, confirming that the nanocomplex has a highly efficient combined tumor treatment effect, providing a scientific experimental basis for the application of new nanocomplexes based on transition metal ion-based nanocarriers in the field of tumor treatment, and expanding the potential application of new nanocomplexes in the field of tumor treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the preparation and application of Fe2O3 / GCN / ICG / DHA; Figure 2 (a), (b), (c), and (d) are TEM images of GCN, Fe2O3 / GCN, Fe2O3 / GCN / ICG, and Fe2O3 / GCN / ICG / DHA, respectively. The inset in (b) is the HRTEM image of Fe2O3. Figure 3 XRD patterns of GCN, Fe2O3 / GCN, Fe2O3 / GCN / ICG, and Fe2O3 / GCN / ICG / DHA; Figure 4 UV absorption spectra of GCN, Fe2O3 / GCN, ICG, Fe2O3 / GCN / ICG, DHA, and Fe2O3 / GCN / ICG / DHA; Figure 5 Fluorescence spectra of GCN, Fe2O3 / GCN, Fe2O3 / GCN / ICG, and Fe2O3 / GCN / ICG / DHA; Figure 6 The absorbance curves of DPBF in different groups at 425 nm change with illumination time; Figure 7 Temperature variation of H2O, GCN, Fe2O3 / GCN, Fe2O3 / GCN / ICG, and Fe2O3 / GCN / ICG / DHA under 808 nm laser (1.8 W) irradiation with time; Figure 8 The temperature variation of different concentrations of Fe2O3 / GCN / ICG / DHA (0, 50, 100, 150, 200 μg / mL) under 808 nm laser (1.8 W) irradiation with time; Figure 9 The temperature variation of Fe2O3 / GCN / ICG / DHA (200 μg / mL) under 808 nm laser irradiation with different powers varies with time; Figure 10 This is the heating and cooling cycle curve of Fe2O3 / GCN / ICG / DHA (200 μg / mL); Figure 11 (a) Single heating and cooling curve of Fe2O3 / GCN / ICG / DHA (200 μg / mL) under 808 nm laser (1.8 W) irradiation; Figure 11 (b) is the linear relationship diagram between cooling time and -ln (θ); Figure 12 DPBF, DHA and Fe 2+ The absorbance change curve of DPBF over time after co-incubation; Figure 13 To measure the cell survival rate after incubation with different concentrations of Fe2O3 / GCN / ICG / DHA for 24 h, MCF-7 and HUVEC cells were used as breast cancer tumor cell models and normal cell models; Figure 14Cell viability of MCF-7 cells after incubation with GCN, DHA, Fe2O3 / GCN / ICG / DHA+NIR, Fe2O3 / GCN / ICG / DHA+H2O2, and Fe2O3 / GCN / ICG / DHA+NIR+H2O2 for 24 h (*p<0.05, **p<0.01, ***p<0.001); Figure 15 Fluorescence imaging of MCF-7 cells after incubation with Fe2O3 / GCN / ICG / DHA (100µg / mL) for 4 hours Figure 16 (a) ROS production in MCF-7 cells after incubation in PBS group, NIR group, GCN group, DHA group, Fe2O3 / GCN / ICG / DHA+H2O2 group, Fe2O3 / GCN / ICG / DHA+NIR group, and Fe2O3 / GCN / ICG / DHA+H2O2+NIR group; Figure 16 (b) Fluorescence intensity analysis of cells in each group; Figure 17 The therapeutic effects of PBS group, NIR group, GCN group, DHA group, Fe2O3 / GCN / ICG / DHA+H2O2 group, Fe2O3 / GCN / ICG / DHA+NIR group, and Fe2O3 / GCN / ICG / DHA+H2O2+NIR group on MCF-7 cells; Figure 18 Cell apoptosis and apoptosis rates of MCF-7 cells after incubation in PBS group, NIR group, GCN group, DHA group, Fe2O3 / GCN / ICG / DHA+H2O2 group, Fe2O3 / GCN / ICG / DHA+NIR group, and Fe2O3 / GCN / ICG / DHA+H2O2+NIR group ( *p<0.05, **p<0.01, ***p<0.001); Figure 19 (a) is the fluorescence imaging of Fe2O3 / GCN / ICG / DHA in mice at different time points (0, 3, 6, 9, 12, 24 h). Figure 19 (b) Fluorescence images of major organs and tumors in Fe2O3 / GCN / ICG / DHA mice; Figure 20 These are infrared thermal images of tumor-bearing mice at different time points after injection of Saline, GCN, Fe2O3 / GCN, Fe2O3 / GCN / ICG, and Fe2O3 / GCN / ICG / DHA via the tail vein; Figure 21Figure 3. Body weight changes (a), relative tumor volume (b), tumor weight (c), pictures of mice in different groups (d), and pictures of tumor tissue (e) in tumor-bearing mice after 14 days of treatment with Saline, NIR, GCN, DHA, ICG+NIR, Fe2O3 / GCN / ICG / DHA, and Fe2O3 / GCN / ICG / DHA+NIR. DETAILED DESCRIPTION
[0022] 1. Preparation of Fe2O3 / GCN / ICG / DHA 1.1 Preparation of carbon nitride nanosheets (GCN) Carbon nitride nanosheets were prepared using a one-step thermal polymerization method. 3.0 g of melamine was weighed and placed in a mortar and ground thoroughly. The ground powder was placed in a muffle furnace and heated to 520 °C at a rate of 5 °C / min for 4 h. After cooling to room temperature, bulk GCN was obtained. The bulk GCN was ground into powder, and 500 mg of the powder was dissolved in 200 mL of deionized water. Ultrasonication was performed for 6 h (600 W) and freeze-dried to obtain carbon nitride nanosheets.
[0023] 1.2 Preparation of ferric oxide / carbon nitride (Fe2O3 / GCN) 0.6 g of the prepared GCN nanosheets and 0.2 g of FeCl₃·6H₂O were dissolved in 20 mL of anhydrous ethanol and stirred at room temperature for 0.5 h to mix thoroughly. The stirred solution was then dried in a 60°C oven. The resulting pale yellow powder was transferred to a covered crucible and placed in a muffle furnace. The temperature was increased to 350°C at a rate of 5°C / min for 2 h to yield a brown-yellow powdered product. This product was dissolved in 15 mL of deionized water, mixed thoroughly, and then transferred to a 15 mL polytetrafluoroethylene reactor and heated at 160°C for 12 h. After cooling to room temperature, the mixture was thoroughly rinsed with ethanol and deionized water to remove unbound FeCl₃·6H₂O. The resulting precipitate was dried in a 60°C oven overnight to yield Fe₂O₃ / GCN.
[0024] 1.3 Preparation of ferric oxide / carbon nitride / indocyanine green (Fe2O3 / GCN / ICG) Solution A was prepared by dissolving 10 mg of Fe₂O₃ / GCN in 10 mL of methanol and sonicating for 30 minutes. Solution B was prepared by dissolving 3 mg of indocyanine green in 10 mL of methanol. Solution B was added to Solution A and stirred at 350 rpm for 12 hours at room temperature in the dark. The resulting reaction product was centrifuged at 10,000 rpm for 15 minutes, and the precipitate was collected and washed several times with anhydrous ethanol and deionized water. The washed product was then dried in a 60°C oven overnight to obtain Fe₂O₃ / GCN / ICG.
[0025] 1.4 Preparation of ferric oxide / carbon nitride / indocyanine green / dihydroartemisinin (Fe2O3 / GCN / ICG / DHA) Disperse 10 mg of the Fe2O3 / GCN / ICG synthesized in 1.3 in 10 mL of anhydrous ethanol to obtain a Fe2O3 / GCN / ICG solution. Dissolve 4 mg of dihydroartemisinin in 5 mL of anhydrous ethanol and add it to the Fe2O3 / GCN / ICG / DHA solution. Stir at room temperature for 24 h. The reaction product is washed alternately with anhydrous ethanol and deionized water to remove free DHA. Dry at 60°C to obtain a Fe2O3 / GCN / ICG / DHA solid.
[0026] 2. Characterization of Fe2O3 / GCN / ICG / DHA The microstructure of the nanocomposite was characterized using a JEM-2100F transmission electron microscope. Figure 2 As can be seen in (a), the prepared GCN has a sheet-like structure, and Fe2O3 nanoparticles with good dispersion are synthesized on the surface of GCN nanosheets by hydrothermal method ( Figure 2 (b)), it can be seen from the inset that the Fe2O3 nanoparticles have obvious lattice fringes with a lattice spacing of 0.25 nm, corresponding to the (104) plane of Fe2O3 NPs. Figure 2 (c) shows that loading ICG has no effect on the sheet structure of Fe2O3 / GCN; after further loading the drug DHA on the surface of Fe2O3 / GCN / ICG ( Figure 2 (d)), the morphology of Fe2O3 / GCN / ICG did not change.
[0027] Figure 3 Figure 2 shows the XRD patterns of GCN, Fe2O3 / GCN, Fe2O3 / GCN / ICG and Fe2O3 / GCN / ICG / DHA. After ICG was modified on the surface of Fe2O3 / GCN and loaded with drug DHA, they all showed typical characteristic diffraction peaks of Fe2O3 and GCN, confirming that ICG and DHA did not affect the crystal structure of Fe2O3 / GCN.
[0028] The distribution of element contents in Fe2O3 / GCN / ICG / DHA is shown in Table 1.
[0029] Table 1
[0030] Figure 4 Figure 3 is the UV absorption spectra of GCN, Fe2O3 / GCN, Fe2O3 / GCN / ICG and Fe2O3 / GCN / ICG / DHA. After loading DHA, the characteristic absorption peak of DHA appeared at 280 nm. This result provides a basis for confirming that DHA was successfully loaded on Fe2O3 / GCN / ICG.
[0031] The fluorescence properties of the materials were studied by fluorescence spectroscopy. Figure 5 ), at the maximum excitation wavelength of 780 nm, Fe2O3 / GCN / ICG and Fe2O3 / GCN / ICG / DHA showed maximum fluorescence emission peaks at 814 nm, confirming that Fe2O3 / GCN / ICG and Fe2O3 / GCN / ICG / DHA have the ability of fluorescence imaging.
[0032] The above experimental results show that Fe2O3 / GCN / ICG / DHA nanocomposite was successfully prepared.
[0033] 3. In vitro performance study of Fe2O3 / GCN / ICG / DHA 3.1 Drug loading determination Drug loading refers to the amount of drug loaded per unit weight of the nanocomplex and is used to evaluate the drug-loading capacity of the nanocomplex. Drug loading experiments were conducted using DHA mass to Fe₂O₃ / GCN / ICG mass ratios of 1:1, 1:1.5, 1:2, 1:2.5, 1:3, and 1:3.5, respectively. After 10 mL of a 1 mg / mL Fe₂O₃ / GCN / ICG solution was mixed and stirred for 24 hours with 10 mL of DHA solutions of varying concentrations, the resulting reaction products were centrifuged at 10,000 rpm for 15 minutes and washed alternately with anhydrous ethanol and deionized water. To measure the DHA drug loading, the supernatant was collected and processed. The supernatant was mixed with 0.2% aqueous NaOH and heated at 55 ± 1°C for 30 minutes to convert the DHA in the supernatant into a compound with characteristic UV absorption. The absorbance at 288 nm was measured using a UV-vis spectrophotometer.
[0034] According to the formula: drug loading capacity (DLC) = [(initial drug mass - supernatant drug mass) / total mass of the nanocomposite] × 100%, it was calculated that the maximum drug loading capacity was 21.23% when the drug loading ratio was 2.5:1, confirming that Fe2O3 / GCN / ICG has the potential to be used as a drug carrier. Therefore, the optimal drug loading ratio of 2.5:1 was used for subsequent experiments.
[0035] 3.2 Drug release studies In order to study the drug release behavior of Fe2O3 / GCN / ICG / DHA under different pH environments, Fe2O3 / GCN / ICG / DHA (1 mg / mL, 5 mL) was dissolved in PBS (pH=7.4 or 5.5). The mixture was incubated at 37°C and centrifuged at different time points (2, 4, 6, 8, 10, 12, 24). The supernatant was mixed with 0.2% NaOH aqueous solution and heated at 55±1°C for 30 min to convert DHA into a compound with UV absorption. The absorbance at 288 nm was measured, and the drug release rate of DHA was calculated using the DHA standard curve.
[0036] The drug release rate of Fe2O3 / GCN / ICG / DHA in PBS with pH=7.4 was 12.61%, while the drug release rate in PBS with pH=5.5 could reach 52.92%, indicating that Fe2O3 / GCN / ICG / DHA has pH-responsive drug release properties.
[0037] 3.3 In vitro photodynamic performance measurement The DPBF probe was used to detect the photodynamic properties of Fe2O3 / GCN / ICG / DHA in vitro. The in vitro photodynamic properties were mainly determined by monitoring the generation of singlet oxygen. When the DPBF probe reacted with singlet oxygen, the diene bond in its molecule was oxidized and destroyed by singlet oxygen to produce a cyclic product, which in turn led to the weakening or disappearance of its characteristic absorption peak at 425 nm.
[0038] The in vitro photodynamic experiment was divided into: ① DPBF group, ② DPBF+NIR group, ③ DPBF+ Fe2O3 / GCN / ICG / DHA group, ④ DPBF+Fe2O3 / GCN / ICG+NIR group, and ⑤ DPBF+ Fe2O3 / GCN / ICG / DHA+NIR group. The concentrations of Fe2O3 / GCN / ICG and Fe2O3 / GCN / ICG / DHA were both 200 μg / mL. A DPBF solution with a concentration of 1.2 mM was prepared as a stock solution. During the experiment, each group was treated as follows: 2 mL of the material solution was mixed with 83 μL of the DPBF stock solution and placed in a quartz cuvette. The solution was irradiated with 808 nm laser (1.8 W) for 10 min, and the absorbance of the above five groups of solutions at 425 nm was measured every 2 min using a UV-vis spectrophotometer.
[0039] Figure 6The ability of DPBF group, DPBF+NIR group, DPBF+ Fe2O3 / GCN / ICG / DHA group, DPBF+Fe2O3 / GCN / ICG+NIR group, and DPBF+Fe2O3 / GCN / ICG / DHA+NIR group to produce ROS in vitro was investigated. After 808 nm laser irradiation, the absorbance of DPBF remained basically unchanged in the DPBF group, DPBF+NIR group, and DPBF+Fe2O3 / GCN / ICG / DHA group. After 808 nm laser irradiation, the absorbance of DPBF at 425 nm in the DPBF+Fe2O3 / GCN / ICG+NIR group and DPBF+Fe2O3 / GCN / ICG / DHA+NIR group gradually decreased with increasing irradiation time, confirming that Fe2O3 / GCN / ICG has the ability to generate ROS under near-infrared laser irradiation and that loading with DHA does not affect the photodynamic properties of the Fe2O3 / GCN / ICG / DHA nanocomplex, providing a basis for subsequent photodynamic therapy at the cellular and animal living levels.
[0040] 3.4 In vitro photothermal performance measurement In order to evaluate the in vitro photothermal performance of Fe2O3 / GCN / ICG / DHA, the photothermal capacity of different groups of solutions was investigated under a fixed laser power (1.8 W) using 808 nm laser as the light source. Figure 7 ), it can be seen that the solution temperature of the H2O group, GCN group, and Fe2O3 / GCN group did not increase significantly after 808 nm laser irradiation for 10 minutes, while the solution temperature of the Fe2O3 / GCN / ICG group and Fe2O3 / GCN / ICG / DHA group increased to 48.1 ℃ and 47.3 ℃, respectively, with the increase of irradiation time. As the material concentration increased and the laser light power increased, the temperature-raising effect of Fe2O3 / GCN / ICG / DHA became better ( Figure 8 and Figure 9 ). Figure 10 By periodically turning the light source on and off to monitor the temperature changes of Fe2O3 / GCN / ICG / DHA, it can be seen from the figure that Fe2O3 / GCN / ICG / DHA has good photothermal stability.
[0041] Figure 11The following are photothermal images of each solution group under 808 nm laser irradiation. After 10 minutes of laser irradiation, the H2O, GCN, and Fe2O3 / GCN groups showed no significant color change. However, the Fe2O3 / GCN / ICG and Fe2O3 / GCN / ICG / DHA groups showed significant color changes that gradually deepened, indicating that Fe2O3 / GCN / ICG / DHA has excellent in vitro photothermal imaging capabilities. These results confirm that Fe2O3 / GCN / ICG / DHA has excellent photothermal properties.
[0042] 3.5 In vitro chemokinetic experiments The mechanism by which the Fe2O3 / GCN / ICG / DHA nanocomposite exerts its chemical kinetic properties is mainly due to the cleavage of peroxide bonds in the DHA molecular structure by ferrous ions, thereby generating carbon-centered free radicals. The DPBF probe was used to evaluate the ability of ferrous ions and DHA to generate C-centered free radicals. The characteristic absorption peak of DPBF at 425 nm gradually decreased with the generation of C-centered free radicals. The C-centered free radical determination experiment was divided into the following five groups: ① DHA group, ② Fe 2+ Group ③ DPBF + Fe 2+ group, ④ DPBF + DHA group, ⑤ DPBF + Fe 2+ + DHA group, the materials in each group were incubated at 37°C for 30 min, and the absorbance changes at 425 nm were measured using a UV-vis spectrophotometer.
[0043] like Figure 12 As shown, DPBF solution has a strong absorption peak at 420 nm. 2+ When DPBF was incubated with DHA or DHA alone, the absorbance of DPBF remained basically unchanged. 2+ After incubation, the absorbance of DPBF decreased significantly within 10 min, indicating that DHA and Fe 2+ The combined effect can generate C-centered free radicals, which can exert a chemical dynamic effect. In addition, the DPBF absorbance shows a downward trend with the increase of incubation time. 4. Study on the cellular performance of Fe2O3 / GCN / ICG / DHA 4.1 Dark cytotoxicity assay The dark toxicity of Fe2O3 / GCN / ICG / DHA on MCF-7 and HUVEC cells was determined by standard MTT assay. Figure 13It can be seen that after incubating the cells with Fe2O3 / GCN / ICG / DHA at a concentration of 0-200 μg / mL for 24 h, the cell viability of MCF-7 and HUVEC cells remained above 80%, indicating that Fe2O3 / GCN / ICG / DHA has good cell biocompatibility.
[0044] 4.2 Cell phototoxicity experiment To evaluate the phototoxicity of Fe2O3 / GCN / ICG / DHA on MCF-7 cells, the cells were incubated with different groups of materials (concentrations ranged from 0 to 200 μg / mL) ( Figure 14 As shown in the figure, after 24 hours of incubation, cell viability remained above 90% in both the GCN and DHA groups. However, after treatment with the Fe2O3 / GCN / ICG / DHA+NIR group (PDT+PTT), the Fe2O3 / GCN / ICG / DHA+H2O2 (250µM) (CDT), and the Fe2O3 / GCN / ICG / DHA+H2O2+NIR group (PDT+PTT+CDT), cell viability in each group decreased significantly to varying degrees. The Fe2O3 / GCN / ICG / DHA+NIR group had a cell viability of 45.71%, while the Fe2O3 / GCN / ICG / DH+H2O2 group had a cell viability of 55.99%. The combined treatment group (Fe2O3 / GCN / ICG / DHA+NIR+H2O2) exhibited the highest cytotoxicity, with a cell viability of only 22.74%.
[0045] 4.3 Cellular uptake experiments Figure 15 Figure 3 shows the uptake of Fe2O3 / GCN / ICG / DHA by MCF-7 cells. Excitation at 405 nm corresponds to the blue fluorescence of GCN, and at 640 nm to the red fluorescence of ICG. Compared with the control group (PBS group), the Fe2O3 / GCN / ICG / DHA group exhibited significant blue and red fluorescence at 405 nm and 640 nm, respectively, indicating that Fe2O3 / GCN / ICG / DHA was successfully taken up by tumor cells via endocytosis.
[0046] 4.4 Intracellular reactive oxygen species determination The DCFH-DA probe was used to detect the level of intracellular reactive oxygen species. Figure 16 As can be seen from (a) and (b), no obvious green fluorescence signals were produced in the PBS group, NIR group, GCN group, and DHA group. The green fluorescence signals produced in the cells of the Fe2O3 / GCN / ICG / DHA+H2O2 group and the Fe2O3 / GCN / ICG / DHA+NIR group were attributed to the Fe 2+The generation of C-center free radicals with DHA and the generation of singlet oxygen by ICG under 808 nm laser irradiation indicate that Fe2O3 / GCN / ICG / DHA has the ability to generate ROS within cells. When Fe2O3 / GCN / ICG / DHA was co-incubated with H2O2 and irradiated with 808 nm near-infrared laser, the intracellular green fluorescence signal was significantly higher than that in the Fe2O3 / GCN / ICG / DHA+H2O2 and Fe2O3 / GCN / ICG / DHA+NIR groups, which is the result of the combined action of singlet oxygen and C-center free radicals.
[0047] 4.5 AM / PI live-dead cell double staining experiment The Calcein-AM / PI Live-Dead Cell Dual Staining Kit can be used to dual-stain live and dead cells. Dead cells exhibit red fluorescence, while live cells exhibit green fluorescence, allowing for visual monitoring of cell survival. Figure 17 Figure 3 shows the survival of MCF-7 cells after incubation with different materials. Cells in the PBS, NIR, GCN, and DHA groups exhibited green fluorescence throughout the field of view, indicating virtually no cell death. Both red and green fluorescence signals were present in the Fe2O3 / GCN / ICG / DHA+H2O2 groups (PDT and PTT groups) and the Fe2O3 / GCN / ICG / DHA+NIR group (CDT group). The Fe2O3 / GCN / ICG / DHA+H2O2 group (PDT and PTT groups) exhibited more red fluorescence than the Fe2O3 / GCN / ICG / DHA+NIR group (CDT group), indicating that the PDT / PTT group exhibited superior tumor-killing efficacy compared to the CDT group. The combined treatment group exhibited red fluorescence throughout the field of view, indicating that virtually all tumor cells underwent apoptosis. These results demonstrate that the Fe2O3 / GCN / ICG / DHA combination therapy effectively induces tumor cell apoptosis.
[0048] 4.6 Cell apoptosis assay Flow cytometry was used to evaluate the tumor therapeutic effect of Fe2O3 / GCN / ICG / DHA. Figure 18 As shown, the apoptosis rates of cells in the PBS, NIR, GCN, and DHA groups were all below 10%. The apoptosis rates of cells in the Fe2O3 / GCN / ICG / DHA+H2O2, Fe2O3 / GCN / ICG / DHA+NIR, and Fe2O3 / GCN / ICG / DHA+H2O2+NIR groups reached 46.6%, 33.87%, and 75.77%, respectively. This indicates that the Fe2O3 / GCN / ICG / DHA nanocomplex can effectively induce apoptosis in tumor cells and has a good anti-tumor effect.
[0049] 5. In vivo experiments on small animals 5.1 Fluorescence imaging of mice The distribution behavior of Fe2O3 / GCN / ICG / DHA in tumor-bearing mice was studied using a multimodal small animal in vivo imaging system. Figure 19 (a) It can be seen that after the tail vein injection of Fe2O3 / GCN / ICG / DHA, the fluorescence intensity of the tumor site of the tumor-bearing mice gradually increased and reached the maximum at 9 h. At 24 h, the fluorescence of the tumor site was significantly weakened, and the fluorescence of the liver area was enhanced, indicating that Fe2O3 / GCN / ICG / DHA was mainly metabolized through the liver. Figure 19 (b) Fluorescence image of the main organs and tumor tissue of another mouse 9 hours after tail vein injection of Fe2O3 / GCN / ICG / DHA. As can be seen from the figure, there is an obvious fluorescence signal in the tumor tissue, indicating that Fe2O3 / GCN / ICG / DHA accumulates most in the tumor site 9 hours after entering the body. This may be because compared with normal tissue, Fe2O3 / GCN / ICG / DHA is easier to penetrate into tumor tissue and stay for a long time.
[0050] 5.2 Photothermal Imaging of Mice Use infrared thermal imager to take photos and record the photothermal imaging effect of tumor-bearing mice. Figure 20 It can be seen that the temperature of the tumor site of tumor-bearing mice injected with normal saline, GCN and Fe2O3 / GCN by tail vein did not change basically after 808 nm laser irradiation for 10 minutes, while the tumor part of mice injected with Fe2O3 / GCN / ICG and Fe2O3 / GCN / ICG / DHA showed a clear temperature increase trend with the increase of irradiation time. The temperature of the tumor site in the Fe2O3 / GCN / ICG / DHA group reached 46.9℃ after 10 minutes of irradiation, indicating that Fe2O3 / GCN / ICG / DHA can effectively accumulate in the tumor site of mice and has good in vivo photothermal imaging effect.
[0051] 5.3 Evaluation of anti-tumor effects in mice Mice were treated with Saline, NIR, GCN, DHA, ICG+NIR, Fe2O3 / GCN / ICG / DHA, and Fe2O3 / GCN / ICG / DHA+NIR for 14 days. The body weight and tumor volume of mice were recorded every two days during the treatment. Figure 21 (a) and Figure 21 (b) After treatment, pictures of mice in each group were taken ( Figure 21 (d) ), the mice were sacrificed and the tumor weight was recorded ( Figure 21 (c) ), taking pictures of tumor tissues in each group ( Figure 21 (e)).
[0052] Figure 21The results of 14-day treatment of mouse tumors with different materials are shown in the figure. The weight of mice in each group remained basically unchanged during the treatment period ( Figure 21 (a) indirectly indicates that Fe2O3 / GCN / ICG / DHA nanocomposite has no obvious toxic side effects on mice. Figure 21 (b) and Figure 21 (c) As can be seen, at the end of the treatment cycle, tumor volumes in the saline, NIR, GCN, and DHA groups increased to 9.1-, 8.9-, 8.6-, and 8.7-fold, respectively, at the start of treatment, with average tumor weights of 1.76 g, 1.78 g, 1.69 g, and 1.81 g, respectively. Tumor volumes in the ICG+NIR and Fe2O3 / GCN / ICG / DHA groups increased to 3.5- and 4.7-fold, respectively, at the start of treatment, with average tumor weights of 0.59 g and 0.68 g, respectively, indicating that PTT / PDT and CDT can inhibit tumor growth to a certain extent. Tumor volume in the Fe2O3 / GCN / ICG / DHA+NIR group decreased to approximately two-thirds of its initial volume, with an average tumor weight of 0.24 g, significantly lower than the six groups mentioned above. Figure 21 (d) and Figure 21 (e) It can be visually observed that at the end of treatment, the tumors in the combined treatment group were significantly smaller than those in the other groups. These results indicate that the Fe2O3 / GCN / ICG / DHA combined treatment has a significant anti-tumor effect.
[0053] 5.4 Biosafety Assessment After treatment, mice were sacrificed and blood counts and biochemical parameters were measured. Blood counts included red blood cell counts (RBC), plasminogen activator (PLT), hemoglobin (HGB), hematocrit (HCT), chromatin (MCV), chromatin hydrochloride (MCHC), and chromatin hydrochloride (MCH). Biochemical parameters included albumin / protease inhibitor (TP), aspartate aminotransferase (AST), and creatinine / urea (CRE / UREA). Results showed no significant differences in these parameters between the treated and control groups, and all parameters were within normal ranges, confirming that Fe2O3 / GCN / ICG / DHA administration did not induce inflammatory responses or liver or kidney dysfunction in the mice. HE staining of mouse tissues revealed no significant pathological changes in the heart, liver, spleen, lungs, or kidneys, indicating that the material did not damage normal organ tissue. Compared to the control group, HE staining of tumor tissues showed significant ablation in the single-treatment group and extensive ablation in the combined treatment group, demonstrating the significant anti-tumor efficacy of Fe2O3 / GCN / ICG / DHA under near-infrared laser irradiation.
Claims
1. A Fe2O3 / GCN / ICG / DHA nanocomposite, characterized in that: The invention comprises: ferric oxide / carbon nitride (Fe2O3 / GCN) as a carrier, the carrier is loaded with photosensitizer indocyanine green (ICG) and drug dihydroartemisinin (DHA).
2. The method for preparing the Fe2O3 / GCN / ICG / DHA nanocomposite according to claim 1, characterized in that: include: Step 1, preparing carbon nitride nanosheets (GCN); Melamine powder was calcined in a muffle furnace at 520°C ± 5°C, and the calcined product was ground and dissolved in deionized water, and then freeze-dried after ultrasonication to obtain carbon nitride nanosheets; Step 2, preparing ferric oxide / carbon nitride (Fe2O3 / GCN); The carbon nitride nanosheets (GCN) and FeCl3·6H2O obtained in step 1 are dissolved in anhydrous ethanol, mixed evenly and dried; the dried powder is transferred to a muffle furnace and heated to 350℃±5℃ to obtain a product, the product is dissolved in deionized water and transferred to a polytetrafluoroethylene reactor at 160℃±5℃ for complete reaction, the obtained product is washed with ethanol and deionized water, and the precipitate obtained after washing is dried to obtain Fe2O3 / GCN; Step 3, preparing ferric oxide / carbon nitride / indocyanine green (Fe2O3 / GCN / ICG); Dissolve Fe2O3 / GCN and indocyanine green in methanol solution respectively, mix the two solutions and stir in the dark, collect the precipitate after centrifugation, wash the precipitate and dry it overnight to obtain Fe2O3 / GCN / ICG; Step 4, preparing ferric oxide / carbon nitride / indocyanine green / dihydroartemisinin (Fe2O3 / GCN / ICG / DHA); Fe2O3 / GCN / ICG and dihydroartemisinin were dissolved in anhydrous ethanol respectively, the two solutions were mixed and stirred, and the obtained reaction product was washed and dried to obtain Fe2O3 / GCN / ICG / DHA solid.
3. The preparation method according to claim 2, characterized in that: In step 1, 3.0 g of melamine was weighed and placed in a mortar and ground thoroughly; the ground powder was placed in a muffle furnace, heated to 520 °C at a heating rate of 5 °C / min, and calcined for 4 h, and then cooled to room temperature to obtain bulk GCN.
4. The preparation method according to claim 3, characterized in that: In step 1, the blocky GCN was ground into powder, 500 mg was dissolved in 200 mL of deionized water, and then ultrasonicated at 600 W for 6 h and freeze-dried to obtain carbon nitride nanosheets.
5. The preparation method according to claim 2 or 4, characterized in that: In step 2, 0.6 g of the prepared GCN nanosheets and 0.2 g of FeCl3·6H2O were weighed and dissolved in 20 mL of anhydrous ethanol, stirred at room temperature for 0.5 h to mix them evenly, and the stirred solution was placed in a 60°C oven for drying; the powder obtained after drying was transferred to a covered crucible and placed in a muffle furnace, and the temperature was increased to 350°C at a heating rate of 5°C / min for reaction for 2 h to obtain a brown-yellow powder reaction product.
6. The preparation method according to claim 5, characterized in that: In step 2, the brown-yellow powdered reaction product was dissolved in 15 mL of deionized water and mixed evenly, then transferred to a 15 mL polytetrafluoroethylene reactor and heated at 160 °C for 12 h. After cooling to room temperature, it was thoroughly washed with ethanol and deionized water to remove unbound FeCl3·6H2O. Finally, the obtained precipitate was placed in an oven at 60 °C and dried overnight to obtain Fe2O3 / GCN.
7. The preparation method according to claim 2 or 6, characterized in that: In step 3, 10 mg of Fe2O3 / GCN was dissolved in 10 mL of methanol solution and ultrasonically treated for 30 min to obtain solution A. 3 mg of indocyanine green was weighed and dissolved in 10 mL of methanol solution to obtain solution B. Solution B was added to solution A and stirred at 350 rpm for 12 h at room temperature in the dark.
8. The preparation method according to claim 7, characterized in that: In step 3, the reaction product obtained after stirring the reaction in the dark was centrifuged at 10,000 rpm for 15 min, and the precipitate was collected and washed with anhydrous ethanol and deionized water; the washed product was placed in an oven at 60° C. and dried overnight to obtain Fe2O3 / GCN / ICG.
9. The preparation method according to claim 2 or 8, characterized in that: In step 4, 10 mg of Fe2O3 / GCN / ICG is dispersed in 10 mL of anhydrous ethanol to obtain a Fe2O3 / GCN / ICG solution; 4 mg of dihydroartemisinin is dissolved in 5 mL of anhydrous ethanol, added to the Fe2O3 / GCN / ICG / DHA solution, stirred at room temperature for 24 h, and the reaction product is obtained. The free DHA is washed alternately with anhydrous ethanol and deionized water; and dried at 60°C to obtain a Fe2O3 / GCN / ICG / DHA solid.
10. Use of the Fe2O3 / GCN / ICG / DHA nanocomposite according to claim 1 in the preparation of anti-tumor drugs.
Citation Information
Patent Citations
Superparamagnetic ferroferric oxide nano particle drug carrier, preparation method and application thereof
CN103961712A
Fe (III)-ART nano particle as well as preparation method and application thereof
CN112057618A
Monatomic iron-doped graphite-phase carbon nitride nano composite material as well as preparation method and application thereof
CN115317607A
Novel multifunctional Chinese and western medicine nanocapsule and preparation method thereof
CN115671279A
Use of artemisinin and derivative thereof in preparation of sensitizer for thermodynamic therapy
WO2022077830A1